Floriculture Crops Economic Outlook for 2014 - Hayk Khachatryan; Alan W. Hodges; Shawn Steed (EDIS)
This 15-page report summarizes industry statistics using data from primary and secondary sources and highlights production and sales trends in the US environmental horticulture industry in 2014. Data sources include the United States Department of Agriculture National Agricultural Statistics Service (USDA/NASS), US Census Bureau, the IBIS World Industry Reports, National Association of Home Builders, S&P/Case-Shiller Home Price Indices, US Bureau of Labor Statistics, University of Florida Bureau of Economic and Business Research, AIA Economics and Market Research Group, and Florida Realtors®. Primary data is collected through the National Nursery Survey, conducted by the Green Industry Research Consortium. Written by Hayk Khachatryan, Alan W. Hodges, and Shawn Steed, and published by the UF Department of Food and Resource Economics, March 2014.